(Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A - Linnert, Christian; Mutterlose, Jörg (Supplement to: Linnert, C; Mutterlose, J (2009): Evidence of increasing surface water oligotrophy during the Campanian-Maastrichtian boundary interval: Calcareous nannofossils from DSDP Hole 390A (Blake Nose). Marine Micropaleontology, 73(1-2), 26-36, https://doi.org/10.1016/j.marmicro.2009.06.006, 2009)
The latest Cretaceous (Campanian–Maastrichtian) is characterized by several global cooling and intermittent warming events. These climatic changes influenced the palaeoceanography substantially, including changes of the deep water sources and surface water currents. One of the most prominent episodes of climatic cooling occurred during the Campanian–Maastrichtian transition. This study focuses on the palaeoclimate and palaeoceanography of the Campanian–Maastrichtian transition by analysing the calcareous nannofossils of DSDP Hole 390A (139.92–126.15 mbsf; Blake Nose). For the examination of calcareous nannofossils sixty samples were processed using the settling technique. Biostratigraphical index taxa (Broinsonia parca constricta, Uniplanarius trifidus, and Tranolithus orionatus) suggest a late Campanian age for the major part of the studied section. The calcareous nannofossils are well preserved, highly abundant (6.80 billion specimens/gram sediment) and diverse (80 species/sample). The assemblages are dominated by Prediscosphaera spp. (20.5%), Watznaueria spp. (20.3%) and Retecapsa spp. (9.8%). Cool water taxa (Ahmuellerella octoradiata, Gartnerago segmentatum, and Kamptnerius magnificus), however, appear less frequently and do not exceed more than 1%. Due to their rarity these cool water taxa do not support the existence of an intense cooling phase during the Campanian–Maastrichtian transition at DSDP Hole 390A. Around 133 mbsf several nannofossil taxa, however, show a distinctive turnover. Mesotrophic species like Discorhabdus ignotus, Zeugrhabdotus bicrescenticus and Zygodiscus exmouthiensis are abundant below 133 mbsf, whereas oligotrophic taxa like Watznaueria spp., Eiffellithus spp. and Staurolithites flavus become common above this level. These changes imply a decrease in the input of nutrients, perhaps caused by a reorganization of ocean currents (Palaeo Gulf Stream) and reduced upwelling.